Financialisation and the limits of circuit theory - Photis Lysandrou (Finance and Society, 2020)
The theory of the monetary circuit aims to provide a highly stylised account of the workings of a modern monetary production economy. While there may have been a time when it succeeded in this aim, that time is over. The key development in the monetary sphere of capitalism over recent decades is the advent of financialisation, a phenomenon that circuit theory cannot explain other than by omitting some of its most important characterising features while indiscriminately dismissing those features that it does address as dysfunctional outgrowths. The fact is that a theory that has the aggregate monetary circuit as its methodological framework and whose sole focus is on the financing needs of firms is simply not flexible enough to accommodate the new reality of financialisation. To make that accommodation what is needed is a framework that is sufficiently elastic as to be able to encompass a broad range of socio-economic factors, most notably those associated with demographic change, as co-drivers of financialisaton. This article argues that a framework based on Marx's commodity principle meets this requirement.
Keywords: 300; Financialisation; circuit theory; demographic change; Marx's commodity principle